Method for manufacturing oxide and carbon nanotube coated LCO positive electrode material

By covering LLZO particles and carbon nanotubes on the surface of the LCO large particles of the lithium battery positive electrode material, forming a conductive network, the problem of insufficient conductivity of lithium batteries is solved, the capacity and voltage withstand performance of lithium batteries is improved, and the battery life is extended. Enhanced security.

CN119297218APending Publication Date: 2025-01-10SHENZHEN TXD TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411222109.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-16
Filing Date
2024-09-02
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The conductivity of existing lithium battery positive electrode materials is insufficient, resulting in poor lithium ion transfer, which easily forms lithium-consuming products, reducing battery life and voltage resistance.

Method used

The LCO positive electrode material coated with oxide and carbon nanotubes is formed by coating LLZO particles and carbon nanotubes of different lengths on the surface of LCO large particles to form a conductive network, improve the transfer capacity of lithium ions and electrons, and reduce internal resistance and secondary reaction.

Benefits of technology

It improves the conductivity and capacity of lithium batteries, extends the battery life, improves the rate performance and voltage withstand performance, reduces high-voltage oxygen release and gas production behavior, and enhances the safety performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297218A_ABST
    Figure CN119297218A_ABST
Patent Text Reader

Abstract

The invention discloses a method for manufacturing an oxide and carbon nanotube coated LCO positive electrode material. The positive electrode material comprises a plurality of positive electrode particles in a positive electrode; the manufacturing process of the positive electrode particle comprises the following steps: step 500: mixing an LLZO (lithium lanthanum zirconium oxide) material with an LCO large particle to form a composite LCO large particle; wherein the LLZO material comprises a plurality of large LLZO particles and a plurality of small LLZO particles; step 510, carrying out aerobic sintering on the composite LCO large particles to obtain sintered powder; after sintering, forming a first LLZO dielectric phase layer between the bottoms of the LLZO large particles and the LCO large particles; a second LLZO dielectric phase layer is formed between the bottoms of the small LLZO particles and the large LCO particles; the method comprises the following steps: step 520, mixing and stirring the sintered powder and CNT (carbon nano tube) in a stirrer to integrally form the composite LCO large particles of which the outer surfaces are coated with the CNT.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery positive electrode material, in particular to a method for manufacturing an LCO positive electrode material coated with oxide and carbon nanotubes. Background Art

[0002] A battery is composed of a positive electrode and a negative electrode. The positive electrode mainly includes a positive electrode substrate and a positive electrode slurry layer coated on the positive electrode substrate, the positive electrode slurry layer includes: a positive electrode slurry containing a binder, and the positive electrode slurry layer also includes: a plurality of positive electrode particles. Positive electrode particles are mainly used in the positive electrode of general solid-state or quasi-solid-state batteries. Positive electrode particles must have conductive or electrical conductivity so that free electrons can migrate in the positive electrode slurry without consuming too much energy due to internal resistance, thereby achieving effective conduction. Therefore, when manufacturing positive electrode particles, it is necessary to consider the use of specific conductive materials to adjust the conductivity of positive electrode particles.

[0003] Traditionally, the material of the positive electrode particles can be selected from LCO (lithium cobalt oxide), LMFP (lithium manganese iron phosphate), etc. or a mixture thereof, and the positive electrode particles are distributed in the positive electrode slurry. There are already a number of technologies in the known art to improve the ability of positive electrode particles made of these materials to conduct lithium ions, but it is currently believed that the conductivity of lithium batteries is still insufficient in actual use. Therefore, it is necessary to modify some materials to further improve the conductivity of positive electrode particles.

[0004] The applicant's other patents have proposed a number of technologies to increase the conductivity of the entire electrode slurry, such as adding carbon nanotubes to the slurry to bridge the positive electrode particles in the positive electrode material, thereby reducing the internal resistance generated by electrons crossing the slurry to another positive electrode conductive unit, thereby improving the conductivity of the entire positive electrode. The applicant's long-term understanding of such technologies also knows that some chemicals such as lithium lanthanum zirconium oxide (LLZO) can produce good lithium battery conductivity.

[0005] Based on the applicant's long experience in battery materials, the applicant hopes to propose a new design that can make the positive electrode of today's solid-state batteries have higher capacity and conductivity, so as to further improve the performance of the battery.

[0006] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0007] The purpose of the present invention is to solve the problems of the above-mentioned known technologies. The present invention proposes a method for manufacturing an oxide and carbon nanotube coated LCO positive electrode material. After the oxide particles (LLZO large and small particles) are coated on the surface of the LCO large particles, although the ion conductivity and protection are improved, the electronic conductivity is partially reduced due to the ceramic properties of the oxide. Electron transfer and ion transfer are interdependent. In order to transfer ions well, in addition to LLZO and the intermediate layer as channels, an electron conductive medium is also important. Therefore, a conductive network composed of carbon nanotubes of various lengths is coated on the outer ring of the composite LCO large particles. The main function of the short-chain carbon nanotubes is to provide short-range electron transfer capability, thereby conducting electrons to make lithium ions more easily transferred in a short range. The main effect of the long-chain carbon nanotubes is the electron transfer capability between multiple LLZO particles (regardless of size) and between the composite LCO large particles and other materials on the plate, so that there is a small electron transfer chain to promote ion transfer, so that the entire composite positive electrode is improved in both electron and ion transfer. The coating effect of CNT and oxide (LLZO large and small particles) also makes it less likely for lithium ions to be blocked on the positive electrode surface due to poor transmission; and then form SEI and other lithium-consuming products with the electrolyte; improve the life of the entire composite positive electrode material (that is, the cycle performance); at the same time, the good lithium ion and electron transfer chain on the composite positive electrode material also makes the composite positive electrode material have better rate performance. When the ion and electron transfer of the composite positive electrode is improved; its side reactions are reduced, and the LLZO particles and the interphase layer provide more protection for the composite positive electrode; the entire positive electrode material is not easy to react with the electrolyte; it is not easily affected by the side reactions caused by the disintegration of the electrolyte and the reaction of the positive electrode under high voltage; and then improve its voltage resistance so that it can be charged and discharged between 4.7V and 4.9V; at the same time, this protective layer further reduces the high-pressure oxygen release and gas production of the positive electrode; improve the overall safety performance of the battery cell.

[0008] In order to achieve the above-mentioned purpose, the present invention proposes a method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material, wherein the positive electrode material is a plurality of positive electrode particles in the positive electrode, and the oxide is LLZO (lithium lanthanum zirconium oxide); wherein the positive electrode particles are mainly used in the positive electrode of general solid-state or quasi-solid-state batteries; wherein the manufacturing process of each of the positive electrode particles comprises the following steps: step 500: mixing the LLZO (lithium lanthanum zirconium oxide) material with a LCO (lithium cobalt oxide) large particle to form a composite LCO large particle; wherein the LCO large particle has a size of 10 microns to 15 microns and is an irregular cube; wherein the LLZO material comprises a plurality of LLZO large particles and a plurality of LLZO small particles; step 510: then aerobic sintering is performed on the composite LCO large particle to obtain a sintered powder; after sintering, the LLZO large particle is distributed in a convex arc shape on the LCO large particle, which is The invention relates to a method for preparing a composite LCO large particle having a structure with a high middle and gentle ends; a first LLZO interphase layer is formed between the bottom of the LLZO large particle and the LCO large particle; the first LLZO interphase layer is mainly formed of LLZO, cobalt oxide and cobalt extension, wherein the cobalt is mainly formed of oxide from the outer layer of the LCO large particle; its function is to provide a better guiding channel for lithium ions; wherein the LLZO small particle is distributed in a convex arc shape on the LCO large particle, with a structure with a high middle and gentle ends; a second LLZO interphase layer is formed between the bottom of the LLZO small particle and the LCO large particle; the second LLZO interphase layer is mainly formed of LLZO, cobalt oxide and cobalt extension oxide; wherein in step 500, the LLZO small particle, the LLZO large particle and the LCO large particle are fully stirred by a mixer so that the three are evenly mixed to form a composite LCO large particle. The steps of this case also include: step 520: placing the sintered powder and CNT, i.e., carbon nanotubes, into a stirrer for mixing and stirring to form the positive electrode particles; after stirring in step 520, the composite LCO large particles with the CNT coated on the outer surface can be formed, and the carbon nanotubes are randomly distributed on the surface of the composite LCO large particles, i.e., the positive electrode particles are formed; and the CNTs of different lengths form different levels of cross-connections on the composite LCO large particles; the short-chain CNTs cross-connect the LLZO large particles and the LCO large particles, and cross-connect the LLZO small particles and the LCO large particles; the long-chain CNTs are used to cover the entire composite LCO large particles to enhance the overall structural strength.

[0009] The features and advantages of the present invention may be further understood from the following description, which is to be read with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Displays the flowchart for this case.

[0011] Figure 2 Displays the structure diagram of this case.

[0012] Figure 3 Shows an example of this case.

[0013] Figure 4 An enlarged schematic diagram showing the structure of this case.

[0014] Figure 5 An enlarged schematic diagram showing the structure of this case.

[0015] Figure 6 Schematic diagram showing the short-chain CNT coating for this case. DETAILED DESCRIPTION

[0016] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0017] Please refer to Figures 1 to 6 , showing the method of manufacturing the LCO positive electrode material coated with oxide and carbon nanotubes of the present invention, wherein the positive electrode material is presented in the positive electrode in the form of a plurality of positive electrode particles 200, and the oxide in this case is LLZO (lithium lanthanum zirconium oxide). The positive electrode particles 200 are mainly used in the positive electrode 100 of a general solid-state or quasi-solid-state battery. The positive electrode 100 mainly includes a positive electrode substrate 10 (such as Figure 3 ); a positive electrode slurry layer 12 is coated on the positive electrode substrate 10, wherein the positive electrode slurry layer 12 comprises: a positive electrode slurry 14 containing a binder, and the positive electrode slurry layer 12 further comprises: a plurality of positive electrode particles 200. The total weight of the plurality of positive electrode particles 200 accounts for 92wt% to 98wt% of the positive electrode slurry layer 12.

[0018] The manufacturing process of each positive electrode particle 200 (please refer to Figure 1 ) are explained as follows:

[0019] Step 500: LLZO (Li7La3ZrO 12 , lithium lanthanum zirconium oxide) material is mixed with a LCO (LiCoO2, lithium cobalt oxide) large particle 22; wherein the LCO large particle 22 has a size of 10 microns to 15 microns and is in an irregular cubic shape. wherein the LLZO material comprises a plurality of LLZO large particles 24 and a plurality of LLZO small particles 26, wherein the lateral size (i.e., the size along the spherical surface) of the LLZO large particle 24 is between 100 nanometers and 200 nanometers, and the lateral size (i.e., the size along the spherical surface) of the LLZO small particle 26 is less than 50 nanometers.

[0020] The total weight of the plurality of LLZO large particles 24 relative to the weight of the single LCO large particle 22 is in a ratio of 0.5wt% to 0.8wt%; the total weight of the plurality of LLZO small particles 26 relative to the weight of the single LCO large particle 22 is in a ratio of 0.1wt% to 0.3wt%.

[0021] The LLZO small particles 26, the LLZO large particles 24 and the LCO large particles 22 are fully stirred by a mixer 50 so that the three are uniformly mixed. The mixer 50 is a three-dimensional mixer or a flat roller mixer.

[0022] The mixing process is to first add the LLZO large particles 24 and the LCO large particles 22 and stir for half of the entire stirring time (step 500-1), and then add the LLZO small particles 26 to complete the entire stirring time (step 500-2). The stirring speed of the mixer 50 is 50 to 100 rpm, and the stirring time is 8 to 12 hours. After stirring, the outer surface of the LCO large particles 22 is covered by a large number of the LLZO large particles 24 and the LLZO small particles 26, and the whole forms a composite LCO large particle 20.

[0023] The LLZO large particles 24 cannot cover the LCO large particles 22 well, and there will be many gaps, so the LLZO small particles 26 must be filled between the gaps of the LLZO large particles 24. Therefore, the use of a mixture of LLZO large and small particles is more stable in terms of process and surface coverage.

[0024] Step 510: Then, the composite LCO large particles 20 are subjected to oxygen sintering, wherein the sintering temperature is 300 to 450° C., the temperature rise rate is 3 to 5° C. / min, and the temperature is maintained at the highest temperature for 1 to 2 hours to obtain a sintered powder 40. Basically, after sintering, the longitudinal dimensions of the LLZO large particles 24 and the LLZO small particles 26 become shorter, the lateral dimensions become wider, and the total volume remains unchanged.

[0025] After sintering, the LLZO large particles 24 are distributed on the LCO large particles 22 in a convex arc shape, with a high middle and flat ends (such as Figure 4 ). A first LLZO interphase layer 25 is formed between the bottom of the LLZO large particle 24 and the LCO large particle 22. The first LLZO interphase layer 25 is mainly formed by oxides of LLZO, cobalt and cobalt extensions (wherein the cobalt is mainly from the outer layer of the LCO large particle 22). Its function is to provide lithium ions with a better guiding channel. The interphase thickness of the first LLZO interphase layer 25 is between 2 and 12 nanometers.

[0026] The first LLZO interphase layer 25 is an interfacial oxygen-deficient layer 251 and an extension layer 252 generated during the sintering process of the LLZO large particles 24 and the LCO large particles 22, wherein the interfacial oxygen-deficient layer 251 contains La2Zr2O7 and La2O3; and the extension layer 252 contains lithium phosphate; and the thickness of both is 1nm to 10nm. The first LLZO interphase layer 25 helps to connect the LCO large particles 22 and the LLZO large particles 24, making them a continuous interface, and the extension layer 252 itself also has the ability of lithium ion conduction, but it is slightly inferior to the LLZO large particles 24. The role of the interfacial oxygen-deficient layer 251 is to serve as an ion conduction connection layer and a protective role. The extension layer 252 will extend on the surface of the LCO large particles 22 and the surface of the LLZO large and small particles to form a thin film.

[0027] The LLZO small particles 26 are distributed on the LCO large particles 22 in a convex arc shape, with a high middle and flat ends (e.g. Figure 5 A second LLZO interphase layer 27 is formed between the bottom of the LLZO small particle 26 and the LCO large particle 22. The second LLZO interphase layer 27 is mainly formed by oxides of LLZO, cobalt, and cobalt extensions (wherein the cobalt is mainly from the outer layer of the LCO large particle 22), and serves to provide a better guiding channel for lithium ions. The thickness of the second LLZO interphase layer 27 is between 2 and 12 nanometers.

[0028] The second LLZO interphase layer 27 is an interfacial oxygen-deficient layer 271 and an extension layer 272 generated during the sintering process of the LLZO small particle 26 and the LCO large particle 22, wherein the interfacial oxygen-deficient layer 271 comprises La2Zr2O7 and La2O3; and the extension layer 272 comprises lithium phosphate; and the thickness of both is 1nm to 10nm. The second LLZO interphase layer 27 helps to connect the LCO large particle 22 and the LLZO small particle 26, making them a continuous interface, and the extension layer 272 itself also has the ability of lithium ion conduction, but it is slightly inferior to the LLZO small particle 26. The interfacial oxygen-deficient layer 271 serves as an ion conduction connection layer and a protective function. The extension layer 252 will extend on the surface of the LCO large particle 22 and the surface of the LLZO large and small particles to form a thin film.

[0029] The interphase layer forms the connection between LCO and LLZO. The interphase layer contains La2Zr2O7 and part of La2O3. When the coating of LLZO particles on LCO particles is more complete, the exposed surface of LCO particles is less, and the probability and amount of side reactions with electrolyte or colloidal substances are reduced, making the positive electrode material more stable. The dielectric layer includes La2Zr2O7 and part of La2O3. The La2Zr2O7 itself also has the ability to conduct lithium ions. Although its ability is not as good as LLZO, it can serve as an ion conductive layer to help conduct lithium ions from LCO to LLZO. LLZO is like a fast tunnel for lithium ion conduction, allowing lithium ions from LCO to pass through the dielectric layer to LLZO and then migrate out and in quickly and effectively. In addition, La2Zr2O7 itself also has the inertness of ceramic compounds, reducing the side reactions between the positive electrode and the electrolyte. Especially under high voltage conditions (>4.5V or even 4.9V), the dielectric layer can provide passivation and protection effects for the LCO material.

[0030] Step 520: The sintered powder 40 and the carbon nanotube (CNT) 30, i.e., CNT30, are then placed in a stirrer 55 for mixing and stirring to form the positive electrode particles 200. The stirring speed of the planetary stirrer or the drum stirrer 55 is 50 to 150 rpm, and the stirring time is 3 to 6 hours. The stirrer is a planetary stirrer or a drum stirrer.

[0031] In this case, the agitator is divided into two types, one is a wet agitator (such as a planetary agitator) and the other is a dry agitator (such as a three-dimensional mixer). The wet agitator has a better effect, but it needs to be dried to remove moisture.

[0032] In this case, the CNT 30 has two lengths: the short-chain CNT 32 has a length between 0.5 microns and 3 microns; the long-chain CNT 34 has a length between 8 microns and 12 microns. The ratio of the overall weight of the short-chain CNT 32 to the overall weight of the long-chain CNT 34 is 5:2, and the overall weight of the CNT 30 accounts for 0.01wt% to 0.5wt% of the total weight of the LCO large particle 22.

[0033] After the stirring in step 520, the composite LCO large particle 20 with the CNT 30 coated on the outer surface can be formed, and the carbon nanotube 30 is randomly distributed on the surface of the composite LCO large particle 20, that is, the positive electrode particle 200 is formed. After the manufacturing process from step 500 to step 520, the size of the LCO large particle 22 is 10 microns to 15 microns; the lateral size (i.e., the size along the spherical surface) of the LLZO large particle 24 is between 100 nanometers and 280 nanometers; the lateral size (i.e., the size along the spherical surface) of the LLZO small particle 26 is between 50 nanometers and 100 nanometers.

[0034] The CNT 30 of different lengths can form different levels of cross-connections on the composite LCO large particle 20. The short-chain CNT 32 can cross-connect the LLZO large particle 24 and the LCO large particle 22, and cross-connect the LLZO small particle 26 and the LCO large particle 22; the long-chain CNT 34 is used to cover the entire composite LCO large particle 20 to enhance the overall structural strength. CNT is a very good conductive material. When it is attached to the composite LCO large particle 20, it forms a shape like a ball of wool (such as Figure 2 ).

[0035] The carbon nanotubes (i.e., CNT 30) are used to increase the electronic conductivity, that is, to form conductive bridges around the various LLZO large particles 24 and the LLZO small particles 26, so that electrons can be conducted on the composite LCO large particles 20. Since the carbon nanotubes have extremely high conductivity, lithium ions can pass through the carbon nanotubes 30 and be conducted between the different LLZO large particles 24, the LLZO small particles 26, and the LCO large particles 22, thereby increasing the conductivity of the entire positive electrode 100 as a whole.

[0036] The LLZO in the LLZO large particles 24 and the LLZO small particles 26 is preferably selected from at least one of Ga-LLZO (gallium-doped lithium lanthanum zirconium compound), Cu-LLZO (copper-doped lithium lanthanum zirconium compound), Ta-LLZO (tantalum-doped lithium lanthanum zirconium compound), Sr-LLZO (strontium-doped lithium lanthanum zirconium compound) and Al-LLZO (aluminum-doped lithium lanthanum zirconium compound).

[0037] Preferably, the LLZO is selected from Cu a X b-LLZO, X is selected from at least one of Ga (gallium), Ta (tantalum), Sr (strontium), Ba (barium), Al (aluminum), where a+b = 0.25-0.8, a>0.1; the technology of doping copper in LLZO is quite difficult, but it can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased and the manufacturing cost is relatively cheap. And when the material is exposed to air, the formation of lithium carbonate is reduced. That is, the surface stability of the entire material during sintering is increased.

[0038] In this case, after the oxide particles (LLZO large and small particles 24, 26) are coated on the surface of the LCO large particle 20, although the ion conductivity and protection are improved, the electronic conductivity is also partially reduced due to the ceramic properties of the oxide. Electron transfer and ion transfer are interdependent. In order to transfer ions well, in addition to the LLZO and the intermediate layer as channels, an electron conductive medium is also very important. Therefore, the outer circle of the composite LCO large particle 20 is coated with a conductive network composed of carbon nanotubes of various lengths. The main function of the short-chain carbon nanotubes is to provide short-range electron transfer capabilities, thereby conducting electrons to make lithium ions more easily transferred in a short range. The main effect of the long-chain carbon nanotubes is the electron transfer capability between multiple LLZO particles (regardless of size) and between the composite LCO large particle 20 and other materials on the plate, so that there is a small electron transfer chain to promote ion transfer, and the entire composite positive electrode is improved in both electron and ion transfer. The coating effect of CNT and oxide (LLZO large and small particles) also makes it less likely for lithium ions to be blocked on the positive electrode surface due to poor transmission; and then form SEI and other lithium-consuming products with the electrolyte; improve the life of the entire composite positive electrode material (that is, the cycle performance); at the same time, the good lithium ion and electron transfer chain on the composite positive electrode material also makes the composite positive electrode material have better rate performance. When the ion and electron transfer of the composite positive electrode is improved; its side reactions are reduced, and the LLZO particles and the interphase layer provide more protection for the composite positive electrode; the entire positive electrode material is not easy to react with the electrolyte; it is not easily affected by the side reactions caused by the disintegration of the electrolyte and the reaction of the positive electrode under high voltage; and then improve its voltage resistance so that it can be charged and discharged between 4.7V and 4.9V; at the same time, this protective layer further reduces the high-pressure oxygen release and gas production of the positive electrode; improve the overall safety performance of the battery cell.

[0039] In summary, the humanized and considerate design of this case is quite in line with actual needs. Its specific improvement of existing deficiencies is obviously a breakthrough in progress compared to the known technology, and it does have an improvement in efficacy, which is not easy to achieve. This case has not been published or disclosed in domestic and foreign literature and markets, and has complied with the provisions of the Patent Law.

[0040] The above detailed description is a specific description of a feasible embodiment of the present invention, but the embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the technical spirit of the present invention should be included in the patent scope of this case.

Claims

1. A method for manufacturing an oxide and carbon nanotube coated LCO positive electrode material, characterized in that: The positive electrode material in the positive electrode is a plurality of positive electrode particles, the oxide is lithium lanthanum zirconium oxide, i.e., LLZO; the positive electrode particles are used in the positive electrode of a general solid-state or quasi-solid-state battery; and the manufacturing process of each positive electrode particle comprises the following steps: Step 500: Mixing LLZO material with a large lithium cobalt oxide particle to form a composite LCO large particle, where lithium cobalt oxide is abbreviated as LCO; wherein the LCO large particle has a size of 10 microns to 15 microns and is in an irregular cubic shape; wherein the LLZO material comprises a plurality of large LLZO particles and a plurality of small LLZO particles; Step 510: Then, the composite LCO large particles are subjected to oxygen sintering to obtain sintered powder; after sintering, the LLZO large particles are distributed on the LCO large particles in a convex arc shape, which is high in the middle and flat at both ends; a first LLZO interphase layer is formed between the bottom of the LLZO large particles and the LCO large particles; the first LLZO interphase layer is mainly formed of LLZO and cobalt oxides and cobalt extensions, wherein the cobalt is mainly formed of oxides from the outer layer of the LCO large particles; Its function is to provide lithium ions with a better conduction channel; The LLZO small particles are distributed on the LCO large particles in a convex arc shape, which is high in the middle and flat at both ends; a second LLZO interphase layer is formed between the bottom of the LLZO small particles and the LCO large particles; the second LLZO interphase layer is mainly formed by LLZO and cobalt oxide and cobalt extensions.

2. The method for manufacturing an oxide and carbon nanotube coated LCO positive electrode material according to claim 1, characterized in that: In step 500, the LLZO small particles, the LLZO large particles and the LCO large particles are fully stirred by a mixer so that the three are evenly mixed to form the composite LCO large particles.

3. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 2, characterized in that: Also included: Step 520: placing the sintered powder and carbon nanotubes (CNT) in a stirrer for mixing and stirring to form the positive electrode particles; After the stirring in step 520, the composite LCO large particle with the CNT coated on the outer surface can be formed, and the carbon nanotubes are randomly distributed on the surface of the composite LCO large particle, that is, the positive electrode particle is formed; and The CNTs of different lengths form different levels of bridging on the composite LCO large particles; the CNTs bridge the LLZO large particles and the LCO large particles and bridge the LLZO small particles and the LCO large particles; and cover the entire composite LCO large particles to enhance the overall structural strength.

4. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: Before sintering in step 520 , the lateral size of the large LLZO particles is between 100 nanometers and 200 nanometers, and the lateral size of the small LLZO particles is less than 50 nanometers.

5. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: The total weight of the plurality of LLZO large particles relative to the weight of the single LCO large particle is in a ratio of 0.5wt% to 0.8wt%; the total weight of the plurality of LLZO small particles relative to the weight of the single LCO large particle is in a ratio of 0.1wt% to 0.3wt%.

6. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: The mixer is a three-dimensional mixer or a flat rolling mixer; The mixing process in step 510 is to first add the LLZO large particles and the LCO large particles and stir for half of the entire stirring time, and then add the LLZO small particles to complete the entire stirring time; the stirring speed of the mixer is 50 to 100 rpm, and the stirring time is 8 to 12 hours. After stirring, the outer surface of the LCO large particles is covered by a large number of the LLZO large particles and the LLZO small particles, and the composite LCO large particles are formed as a whole.

7. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: The sintering temperature in step 520 is 300 to 450° C., the temperature rise rate is 3 to 5° C. / min, and the temperature is maintained at the highest temperature for 1 to 2 hours to obtain the sintered powder; basically, after sintering, the longitudinal dimensions of the large LLZO particles and the small LLZO particles become shorter, the lateral dimensions become wider, and the total volume remains unchanged.

8. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 1, characterized in that: The dielectric thickness of the first LLZO dielectric layer and the second LLZO dielectric layer is between 2 and 12 nanometers.

9. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 1, characterized in that: The first LLZO interphase layer is an oxygen-deficient layer and an extension layer generated during the sintering process between the LLZO large particles and the LCO large particles; the oxygen-deficient layer comprises La2Zr2O7 and La2O3; and the extension layer comprises lithium phosphate; the thickness of both layers is 1nm to 10nm; the first LLZO interphase layer helps to connect the LCO large particles with the LLZO large particles, so that they form a continuous interface; The second LLZO dielectric layer is an oxygen-deficient interface layer and an extension layer generated during the sintering process of the LLZO small particles and the LCO large particles; the components of the oxygen-deficient interface layer include La2Zr2O7 and La2O3; and the components of the extension layer include lithium phosphate; the thickness of both is 1nm to 10nm; the second LLZO dielectric layer helps to connect the LCO large particles and the LLZO small particles, making them a continuous interface, and the extension layer itself also has the ability of lithium ion conductivity, but it is slightly inferior to the LLZO small particles. The function of the oxygen-deficient interface layer is an ion conduction connection layer and a protective function.

10. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: In step 520, the agitator is a planetary agitator or a drum agitator; the agitation speed of the planetary agitator or the drum agitator is 50 to 150 rpm, and the agitation time is 3 to 6 hours.

11. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: The CNTs include short-chain CNTs for bridging the LLZO large particles and the LCO large particles and bridging the LLZO small particles and the LCO large particles; and long-chain CNTs for coating the entire composite LCO large particles to enhance the overall structural strength; and The length of the short-chain CNT is between 0.5 micrometers and 3 micrometers; the length of the long-chain CNT is between 8 micrometers and 12 micrometers.

12. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 11, characterized in that: The ratio of the total weight of the short-chain CNT to the total weight of the long-chain CNT is 5:2, and the total weight of the CNT accounts for 0.01wt% to 0.5wt% of the total weight of the LCO large particles.

13. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 3, characterized in that: After the sintering and stirring in the above steps, the LCO large particles have a size of 10 micrometers to 15 micrometers; the lateral size of the LLZO large particles is between 100 nanometers and 280 nanometers; and the lateral size of the LLZO small particles is between 50 nanometers and 100 nanometers.

14. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 1, characterized in that: The LLZO in the large LLZO particles and the small LLZO particles is selected from at least one of Ga-LLZO, Cu-LLZO, Ta-LLZO, Sr-LLZO and Al-LLZO.

15. The method for manufacturing an oxide and carbon nanotube coated LCO positive electrode material according to claim 1, characterized in that: Wherein the LLZO is selected from Cu a X b -LLZO, wherein X is selected from at least one of gallium, tantalum, strontium, barium and aluminum; the structure is more stable, the passage of lithium ions is smoother, and the sintering speed is increased; and when the material is exposed to air, the formation of lithium carbonate is reduced.

16. The method for manufacturing an oxide and carbon nanotube-coated LCO positive electrode material according to claim 15, characterized in that: The Cu a X b -a+b=0.25-0.8 in LLZO, a>0.

Citation Information

Patent Citations

  • Method for coating anode material with ion-electron mixed electronic conducting garnet structure

    CN109524654A

  • Coated composite positive electrode material as well as preparation method and application thereof

    CN111682187A

  • Positive electrode active material and high-voltage lithium ion battery comprising same

    CN112542583A

  • Lithium battery core-shell positive electrode material, lithium battery containing lithium battery core-shell positive electrode material and preparation method of lithium battery

    CN113871588A

  • Battery positive electrode material and manufacturing method thereof

    CN114784247A